Effect of solar irradiation, substrate type and environment on the growth and ornamental quality of Euphorbia cotinifolia plants - Aguilar-Luna, Jesús; Hernández-Vargas, Liliana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Euphorbia cotinifolia L. is an ornamental plant of economic importance due to the red-purple color of its foliage. The objective of this research was to evaluate the effect of solar irradiation, substrate type and environment on the growth and ornamental quality of E. cotinifolia plants propagated from semi-woody cuttings. Two experiments were conducted from June 2022 to March 2023, in Tetela de Ocampo and Huitzilan de Serdan, Puebla, Mexico. Each experiment had 20 treatments. The experiments had a 2x5x2 factorial design; factor 1 was growth environments, its levels: temperate climate (STC), and subtropical (SHC). Factor 2 was solar irradiation, its levels: 80, 240, 347, 394, and 571 µmol.m-2.s-1. Factor 3 was the type of substrate, its levels: river sand with peat moss (AT), and forest soil with perlite (SP). At 243 days after rooting, the highest values were: 32.98 cm for terminal shoot growth, 4.80 mm.day-1 in growth rate, 1.76 in robustness index, 1.32 in Dickson's index. The maximum anthocyanin concentration was 4.94 mg.g-1 in red-purple leaves. The highest values and the red-purple color of the foliage (quality indicator) occurred when the plants were grown on AT substrate, at 571 µmol.m-2.s-1 in SHC climate. It is concluded that in tropical climate, plants develop with better quality; river sand with peat moss is recommended as substrate, and exposure to high light intensities.